2016
DOI: 10.1002/jso.24169
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive surgery and HIPEC offers similar outcomes in patients with rectal peritoneal metastases compared to colon cancer patients: a matched case control study

Abstract: Cytoreduction and HIPEC in selected patients with rectal PM is feasible and provides similar outcomes as in colon cancer patients. Rectal PM should not be regarded a contra-indication for cytoreduction and HIPEC in selected patients. J. Surg. Oncol. 2016;113:548-553. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…The most recent and largest study included 29 rectal cancer patients and reported similar recurrence and survival rates compared with colon cancer patients, with 5-year survival rates of ~30% in both groups 69. Similar results were found in two smaller retrospective studies 70,71.…”
Section: Rectal Origin Of Pmsupporting
confidence: 64%
“…The most recent and largest study included 29 rectal cancer patients and reported similar recurrence and survival rates compared with colon cancer patients, with 5-year survival rates of ~30% in both groups 69. Similar results were found in two smaller retrospective studies 70,71.…”
Section: Rectal Origin Of Pmsupporting
confidence: 64%
“…1). Of the 24 cohort studies, six 18,34,37,40,44,47 were prospective and the remaining 18 11,20,[31][32][33]35,36,38,39,[41][42][43]45,46,[48][49][50][51] were retrospective (Table S1, supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies 20,34,36,40,43,47,53,54 reported on the influence of a rectal or colonic primary on OS and six presented adequate data to be included in the meta-analysis. The pooled unadjusted HR for rectal primary (compared with colonic primary) was 1⋅48 (95 per cent c.i.…”
Section: Rectal or Colonic Primarymentioning
confidence: 99%
“…Hyperthermal intraperitoneal chemotherapy has been applied to treat peritoneal carcinomatosis for gastric[ 17 - 19 ], colorectal[ 20 ], ovarian[ 21 ], and peritoneal mesothelioma[ 22 ] and has aided in prolonged long-term survival in selected patients[ 23 - 26 ]. In HIPEC, intraperitoneal free cancer cells and the serous surface of the bowel and peritoneum are exposed to high concentrations of chemotherapy agents.…”
Section: Discussionmentioning
confidence: 99%